Piroxicam inhibits herpes simplex virus type 1 infection in vitro - Astani, Akram; Albrecht, U.; Schnitzler, Paul (Die Pharmazie, 2015)
Piroxicam is a potent, nonsteroidal, anti-inflammatory agent (NSAID) which also exhibits antipyretic activity. The antiviral effect of piroxicam against herpes simplex virus type 1 (HSV-1) was examined in vitro on RC-37 monkey kidney cells using a plaque reduction assay. Piroxicam - was dissolved in ethanol or dimethylsulfoxide (DMSO) and the 50% inhibitory concentration (IC50) was determined at 4 μg/ml and 75 μg/ml, respectively. The IC50 for the standard antiherpetic drug acyclovir was determined at 1.6 μM. At non-cytotoxic concentrations - of these piroxicam solutions, plaque formation was significantly reduced by 62.4% for ethanolic piroxicam and 72.8% for piroxicam in DMSO. The mode of antiviral action of these drugs was assessed by time-on-addition assays. No antiviral effect was observed when cells were incubated with piroxicam - prior to infection with HSV-1 or when HSV-1 infected cells were treated with dissolved piroxicam. Herpesvirus infection was, however, significantly inhibited when HSV-1 was incubated with piroxicam prior to the infection of cells. These results indicate that piroxicam affected the virus before - adsorption, but not after penetration into the host cell, suggesting that piroxicam exerts a direct antiviral effect on HSV-1. Free herpesvirus was sensitive to piroxicam in a concentration-dependent manner and the inhibition of HSV-1 appears to occur before entering the cell but not after - penetration of the virus into the cell. Considering the lipophilic nature of piroxicam, which enables it to penetrate the skin, it might be suitable for topical treatment of herpetic infections.